A novel and facile method for detecting the lattice orientation of MoS2 tribological surface using the SPSA process. (5th December 2017) - Li, Meng; Zhang, Yu; Yu, Peng; Xi, Ning; Wang, Yuechao; Liu, Lianqing
Abstract: Lattice orientation detection techniques are crucial for two-dimensional materials as many unusual properties, such as electronic, optical, catalytic and magnetic properties, are closely related to particular lattice orientations. Herein, we propose a novel, low-cost and convenient detection technique, referred to as a single-line-scan power spectrum analysis (SPSA), which is established based on the power spectrum analysis of friction information that is extracted from an atomic-resolution lateral friction microscopy image. By analysing the characteristics of the friction information and the corresponding frequency spectrum obtained from the tribological surface of MoS2, we innovatively establish a relationship between the frequency characteristics and lattice orientation and ultimately propose our SPSA, which enables detection of the direct lattice orientation using the frequency characteristic values of an arbitrary line on an atomic image. The experimental results further verify the effectiveness and convenience of the SPSA process. Graphical abstract: Highlights: Periodic and symmetrical characteristic of the friction force on MoS2 tribological surface were observed Distinct frequency spectrum characteristics of the friction signals for various lattice orientations were observed Relationship between the frequency and lattice orientation was established Single-line-scan power spectrum analysis process for lattice orientation detection was proposed